Model of Individual Constitutional Complaint Subject to Commonwealth of Independent States Members’ Legislation: a Comparative Legal Analysis - V. S. Kukhlivskiy (Vestnik MGIMO-Universiteta)
CIS members legislation regulating judicial proceedings on individual constitutional complaints is in the process of development, the relevant problems are debated by leading experts on national and international level. In view of the aforesaid this article is devoted to core concept of constitutional complaint - the model of complaint and contains comparative legal analysis of models incorporated in legislation of CIS members in different historical periods. The author proposes to enlarge the list of objects of constitutional complaint so that it includes all types of normative acts as well as individual acts, i.e. to introduce the model of full constitutional complaint. The named measures are aimed to strengthen protection of constitutional human rights in Russia and also to decrease the number of complaints against Russia filed to European Court of Human Rights.